The Dynamics of Torture and Mass Murder in the Story of Ashab Al-Ukhdud: A Tafsir Analysis of the Legal and Humanitarian Aspects in Q.S. Al-Buruj According to Sayyid Qutb - Muhammad Syamsul Munir; Masruhan (Penerbit Hellow Pustaka, 2025)
This study analyzes the interpretation of legal and humanitarian aspects in Surah Al-Buruj, according to Sayyid Qutb in Fi Zilal al-Qur'an, to understand the dynamics of torture in the story of Ashab Al-Ukhdud. Through a qualitative methodology and thematic interpretation approach, the study examines Sayyid Qutb's thoughts on the story of Ashab al-Ukhdud and its relevance to modern social, political, and humanitarian issues. The research highlights the importance of divine justice as a means of resistance against unjust rulers and relates the story of Ashab Al-Ukhdud to the challenges of genocide and human rights violations. The findings emphasize the integration of legal and humanitarian values with Qur'anic texts in contemporary tafsir, contributing to a better understanding of how these values can be applied in a modern context. This study offers insights into the interpretation of Qur'anic texts and their implications for addressing current societal issues..